BIOCHEMICAL ALTERATIONS IN POSTMENOPAUSAL WOMEN HAVING OSTEOPORIC RISK - Sharma, Preeti; PRADEEP KUMAR; RACHNA SHARMA; GAURAV GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Abstract Objective: Osteoporosis is the most common disease worldwide, nutritional factors may play a significant role in the progression of the disease. The aim of this study was to assessment of various biochemical parameters in the postmenopausal women with osteoporosis or osteopenia. Material & Methods: In this hospital based study total 70 postmenopausal women, 45 to 80 year of age group, were studied. They were categorised in two groups as case I and Case II on the basis of diagnosis osteoporosis or osteopenia respectively. The bone mineral density using T score was estimated for diagnosis of osteoporosis or osteopenia. Bone mineral markers i.e. total, calcium and ionized calcium was estimated by colorimetric method. Serum phosphate was estimated by direct method and alkaline phosphatase was measured by kinetic method. Biochemical parameters i.e. urea was estimated by diacetyl monoxime method. Serum albumin and serum creatinine were measured by BCG method and Jaffe's method respectively. Serum uric acid and magnesium were estimated by colorimetric method. Results: Total calcium and ionized calcium were significant (<0.05) between the groups. The levels of serum phosphate and alkaline phosphatase were higher in osteoporotic group but the results were not significant between the groups. Serum urea and serum albumin was comparatively higher and lower in osteoporotic group respectively but the findings were not significant between the groups. The significant results of serum creatinine, serum uric acid and serum magnesium were obtained while comparing between osteoporotic patients and osteopenia patients. The levels were higher in osteoporosis group. There was negative association of alkaline phosphatase with serum calcium and negative association with serum phosphate and uric acid. Conclusion: Biochemical alterations are characterized in osteoporotic as well as osteopenic patients. Monitoring of these parameters may be beneficial while giving the treatment to these patients for prevention the risk of other life threatening risks. Â  Keywords: Osteoporosis, osteopenia, Alkaline Phosphatase, Serum Creatinine, Postmenopause